Transthoracic Echocardiography of the Neonatal Laboratory Piglet - Stephan Schwarz; Miriam Kalbitz; Helmut D. Hummler; Helmut D. Hummler; Marc R. Mendler (Frontiers Media S.A., 2019)
Background: Newborn piglets are commonly used in biomedical research. However, cardiovascular imaging of this species is quite challenging. For point of care diagnostics of heart function transthoracic echocardiography may be used, which appears to differ comparing newborn piglets with adult pigs. To date, there are few data or studies on the feasibility and quality of measurement of functional echocardiographic parameters in very small neonatal piglets.Objectives: To study the feasibility of transthoracic echocardiography in very small newborn piglets in supine position.Methods: In 44 anesthetized and intubated newborn piglets, positioned in supine position [age 32 h (12-44 h), weight 1,220 g (1,060-1,495 g), median (IQR)] transthoracic echocardiography was performed using a point of care ultrasound device (M-Turbo©, FujiFilm SonoSite BV, Amsterdam, Netherlands), and a standard ultrasound transducer.Results: Using 2D- and M-mode-imaging left- and right-sided heart structures were accessible to transthoracic echocardiography in neonatal piglets. Diameters of the interventricular septum, the left ventricle, and the posterior wall were measured and ejection fraction and shortening fraction was calculated. Both left and right ventricular outflow tract could be imaged, and ventricular filling and systolic function could be evaluated. Furthermore, we were able to assess shunts of fetal circulation, such as patent ductus arteriosus, structure of the heart valves and congenital heart defects including ventricular septal defect.Conclusions: In summary, transthoracic echocardiography is feasible for assessment of cardiovascular function even in very small newborn laboratory piglets in supine position.